Great Recession and club convergence in Europe: A cross‐country, cross‐region panel analysis (2000–2015). (12th March 2020) - Mazzola, Fabio; Pizzuto, Pietro
Abstract: The paper aims at investigating the impact of the Great Recession on per capita GDP convergence process across European regions and countries. Using the time‐varying factor model developed by Phillips and Sul for the period 2000–2015 and two different merging procedures to identify clubs, we provide evidence of the diverging impact of the Great Recession "between" the higher and the lower convergence clubs at both regional and country levels as well as of the strengthening of the convergence process "within" most clubs. In addition, we add further evidence to the common belief of a "multi‐speed" Europe by contrasting Eastern European countries' and regions' behavior vis‐à‐vis original European members' one, and by identifying the factors that affect club membership and resilience to the recent economic downturn. We find that the membership in the higher clubs and resilience to the Great Recession are positively affected by the presence of several local‐specific factors and macroeconomic characteristics.